Demonstration of antibody and cellular immune response to brain extract in West and Lennox-Gastaut syndromes - Norma G. S. Mota; M. Thereza Rezkallah-Iwasso; M. Terezinha S. Peraçoli; Terezinha C. B. Montelli (Arquivos de Neuro-Psiquiatria, 1984)
We investigated humoral and cellular immune response to brain tissues in 15 patients with West syndrome, in 9 patients with Lennox-Gastaut syndrome and in 20 healthy children. High levels of a precipitating antibody to a saline extract of brain tissue were detected in all patients; leucocyte migration inhibition test with the same antigen was found to be positive in most of them. The role of this autoimmune response in the pathogenesis of West and Lennox-Gastaut syndromes remains to the elucidated.